Institutional changes and transaction costs: Exchange arrangements in Tanzania's coffee market - Temu, Anna A. (International Food Policy Research Institute, 2009)
This case study presents an assessment of institutional and organizational changes in Tanzania’s coffee market following market liberalization. It provides an understanding of how institutions can influence transaction costs in the exchange of agricultural commodities. The discussion is based on the literature on industrial organization, institutional economics, and transaction-costs theory discussed in previous chapters. Market liberalization policies have been implemented in several countries in Africa since the mid-1980s. In this study the structure of the coffee market before and after liberalization is examined and market conduct, institutions, and organizational linkages that influence market performance are identified. The aim is to assess the performance of the market after liberalization, identify sources of transaction costs, and identify constraints on market performance.